ผลของการออกกำลังกายแบบก้าวตามตารางต่อสมรรถภาพทางกาย ในผู้สูงอายุ - แสงสว่าง พรรณทิพ; จินตนาวัฒน์ โรจนี; สุคำวัง กนกพร (Journal of Thailand Nursing and Midwifery Council, 2016)
บทคัดย่อ: วัตถุประสงค์ของการวิจัย: เพื่อศึกษาผลของการออกกำลังกายแบบก้าวตามตารางต่อสมรรถภาพทางกายในผู้สูงอายุ การออกแบบวิจัย: การวิจัยเชิงทดลอง แบบสองกลุ่มวัดก่อนและหลังการทดลอง วิธีดำเนินการวิจัย: กลุ่มตัวอย่างคือ ผู้สูงอายุที่อาศัยอยู่ในตำบลหนองหอย และตำบลท่าศาลา อำเภอเมือง จังหวัดเชียงใหม่ จำนวน 49 ราย โดยการสุ่มแบบหลายขั้นตอนและทำการสุ่มอย่างง่าย เป็นกลุ่มทดลอง 23 ราย และกลุ่มควบคุม 26 ราย ซึ่งกลุ่มทดลองได้รับการออกกำลังกายแบบก้าวตามตาราง นานครั้งละ 55 นาที 3 ครั้งต่อสัปดาห์ อย่างต่อเนื่อง 12 สัปดาห์ โดยผู้วิจัยเป็นผู้นำการออกกำลังกาย ส่วนกลุ่มควบคุมไม่ได้รับการ ออกกำลังกายแบบก้าวตามตาราง การประเมินสมรรถภาพทางกาย โดยการวัด 2 ตัว แปร คือ 1) ความยืดหยุ่นของกล้ามเนื้อและข้อต่อ โดยวิธีการนั่งโน้มตัวไปข้างหน้า 2) ความทนทานของปอดและหัวใจ โดยประเมินความสามารถในการเดินบนพื้นราบในเวลา 6 นาทีการวิเคราะห์ข้อมูลใช้สถิติทดสอบค่าที ผลการวิจัย: ความยืดหยุ่นของกล้ามเนื้อและข้อต่อ ความทนทานของปอดและหัวใจของผู้สูงอายุในกลุ่มที่ออกกำลังกายแบบก้าวตามตาราง มากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 ความยืดหยุ่นของกล้ามเนื้อและข้อต่อ ความทนทานของปอดและหัวใจของผู้สูงอายุ ภายหลังการออกกำลังกายแบบก้าวตามตาราง มากกว่าก่อนการออกกำลังกายแบบก้าวตาม ตารางอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 ข้อเสนอแนะ: การออกกำลังกายแบบก้าวตามตารางสามารถนำไปใช้เป็นแนวทางในการส่งเสริมสมรรถภาพทางกายของผู้สูงอายุได้ Abstract: Objectives: To study possible contribution of square-stepping exercise to elderly people’s physical fitness. Design: Experimental two-group research with a pre-test and a post-test. Implementation: This study was conducted on a sample of 49 elderly residents of Nong Hoy and Tha Sala subdistricts, Mueang district, Chiang Mai province. Selection of subjects was by means of simple random sampling and multi-stage sampling. Twenty-three of the participants were placed in the experimental group, and the remaining 26 in the control group. Only the experimental group members were required to perform three 55-minute researcher-guided sessions of square-stepping exercise every week for a total of 12 weeks. The participants’ physical fitness was measured according to two variables: (1) musculoskeletal flexibility, using a sit-andreach test; and (2) cardiorespiratory endurance, using a 6-minute walk test (6MWT). The data were analysed using t-test statistics. Results: The experimental group displayed significantly greater degrees (0.05) of musculoskeletal flexibility and cardiorespiratory endurance than did the control group. Also, after the square-stepping exercise programme, the experimental group showed significant improvement (0.05) of their musculoskeletal flexibility and cardiorespiratory endurance. Recommendations: Square-stepping exercise should be adopted as a means of promoting physical fitness in elderly people.